Gold&silver recovery from jewelry waste with combination of physical and physicochemical methods - Burat, Fırat; Baştürkcü, Hüseyin; Özer, Mustafa (Elsevier BV, 2019)
The recovery of precious metals can be successfully managed from waste which is considered to be secondary sources of raw material. Waste derived from jewelry activity falls in this category, and represents an essential component of precious metals. The most important metals in the jewelry sector are gold (Au) and silver (Ag). As a result of workmanship, the thin metals, jewel parts and metallic powders are generated and the dust produced from jewelry workshops is of great importance. This paper describes the concentration and recovery of Au and Ag from floor sweeping waste at jewelry workshops by physical (shaking table, multi gravity separator (MGS), Knelson and Falcon concentrators) and physicochemical methods (froth flotation). Experimental results demonstrated that the gravity beneficiation methods were effective for eliminating much of the waste matrix. A heavy fraction with 701 g/t Au and 6017 g/t Ag content was obtained from a feed assaying 183 g/t Au and 1835 g/t Ag by shaking table separator. For enhanced beneficiation, the middling's from tabling were subjected to centrifugal separator and Ag grade increased from 848 g/t to 7812 g/t. Au and Ag fractions discharged in tailings from gravity and centrifugal separations were successfully concentrated using froth flotation and led to a total recovery around 92% both for Au and Ag.
Keywords: Silver; Jewelry; Gold